1995
DOI: 10.1101/gad.9.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel serine/threonine kinase and a novel 15-kD protein as potential mediators of the gamma interferon-induced cell death.

Abstract: Programmed cell death is often triggered by the interaction of some cytokines with their cell surface receptors. Here, we report that ~/interferon (IFN-~/) induced in HeLa cells a type of cell death that had cytological characteristics of programmed cell death. In this system we have identified two novel genes whose expression was indispensable for the execution of this type of cell death. The rescue was based on positive growth selection of cells after transfection with antisense cDNA expression libraries. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
520
0
3

Year Published

1996
1996
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 555 publications
(539 citation statements)
references
References 58 publications
16
520
0
3
Order By: Relevance
“…Therefore, this kinase was named ZIP kinase, for zipper interacting protein kinase. Moreover, these authors claimed that ectopic overexpression of ZIP kinase in NIH3T3 cells induced apoptosis, as might be expected from its homology to DAP kinase the latter of which is involved in interferon g-induced cell death (Deiss et al, 1995;Cohen et al, 1997). In our hands Dlk, when expressed as GFPfusion protein, did not exhibit apoptotic activity to a signi®cant extent.…”
Section: Introductionsupporting
confidence: 57%
“…Therefore, this kinase was named ZIP kinase, for zipper interacting protein kinase. Moreover, these authors claimed that ectopic overexpression of ZIP kinase in NIH3T3 cells induced apoptosis, as might be expected from its homology to DAP kinase the latter of which is involved in interferon g-induced cell death (Deiss et al, 1995;Cohen et al, 1997). In our hands Dlk, when expressed as GFPfusion protein, did not exhibit apoptotic activity to a signi®cant extent.…”
Section: Introductionsupporting
confidence: 57%
“…[1][2][3][4] Though a large number of physiological examples in which DAPk is pivotal for programmed cell death has accumulated over the years, only a few specific activating signals as well as relevant substrates and interacting proteins have been described. In this work, we demonstrate DAPk as a sensor of oxidative stress and describe PKD as a novel target of DAPk that mediates JNK activation and caspase-independent cell death under oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…1 It has since been characterized as a tumor suppressor protein whose expression is greatly reduced or lost in a significant number of human malignancies. 2,3 DAPk belongs to the family of Ca 2 þ -CAMregulated kinases and contains a Ca 2 þ -CAM binding domain proximal to the catalytic domain.…”
mentioning
confidence: 99%
“…DAP kinase is a member of the CaMK family that was originally identi®ed as an essential molecule in interferon (IFN) -g-induced apoptosis in HeLa cells (Deiss et al, 1995;Cohen et al, 1997). It was shown that the reduced expression of DAP kinase mediated by antisense mRNA protected HeLa cells from apoptosis induced by IFN-g, and overexpression of DAP kinase induced apoptosis .…”
Section: Introductionmentioning
confidence: 99%